Naegleria genus pangenome reveals new structural and functional insights into the versatility of these free-living amoebae - Dereeper, Alexis; Allouch, Nina; Guerlais, Vincent; Garnier, Maëlle; Ma, Laurence; De Jonckheere, Johan F.; Joseph, Sandeep J.; Ali, Ibne Karim M.; Talarmin, Antoine; Marcelino, Isabel (Frontiers in Microbiology, 2023)
Free-living amoebae of the Naegleria genus belong to the major protist clade Heterolobosea and are ubiquitously distributed in soil and freshwater habitats. Of the 47 Naegleria species described, N. fowleri is the only one being pathogenic to humans, causing a rare but fulminant primary amoebic meningoencephalitis. Some Naegleria genome sequences are publicly available, but the genetic basis for Naegleria diversity and ability to thrive in diverse environments (including human brain) remains unclear. Herein, we constructed a high-quality Naegleria genus pangenome to obtain a comprehensive catalog of genes encoded by these amoebae. For this, we first sequenced, assembled, and annotated six new Naegleria genomes. Genome architecture analyses revealed that Naegleria may use genome plasticity features such as ploidy/aneuploidy to modulate their behavior in different environments. When comparing 14 near-to-complete genome sequences, our results estimated the theoretical Naegleria pangenome as a closed genome, with 13,943 genes, including 3,563 core and 10,380 accessory genes. The functional annotations revealed that a large fraction of Naegleria genes show significant sequence similarity with those already described in other kingdoms, namely Animalia and Plantae. Comparative analyses highlighted a remarkable genomic heterogeneity, even for closely related strains and demonstrate that Naegleria harbors extensive genome variability, reflected in different metabolic repertoires. If Naegleria core genome was enriched in conserved genes essential for metabolic, regulatory and survival processes, the accessory genome revealed the presence of genes involved in stress response, macromolecule modifications, cell signaling and immune response. Commonly reported N. fowleri virulence-associated genes were present in both core and accessory genomes, suggesting that N. fowleri' s ability to infect human brain could be related to its unique species-specific genes (mostly of unknown function) and/or to differential gene expression. The construction of Naegleria first pangenome allowed us to move away from a single reference genome (that does not necessarily represent each species as a whole) and to identify essential and dispensable genes in Naegleria evolution, diversity and biology, paving the way for further genomic and post-genomic studies.